Education, unemployment, and economic growth in Malaysia / Tatiana Eddy Tabak - Eddy Tabak, Tatiana (2012)
The economic progress and development of a country made by most countries is caused by many factors. Education is often cited as a major contributing factor. Many developing countries realized the importance of education, Malaysia also no exempt. The government of Malaysia has started giving more attention to improve the quality of education. Educational attainment was not indirectly effect the economic growth but it has relationship with labor productivity. This paper also discussed about the unemployment and economic growth. There is inverse relationship between unemployment and economic growth. In this paper, we used time series data obtained from World Data Bank and The Department of Statistic to collect the data of educational attainment, data of unemployment and data of Economic Growth of this country from 1982 until 2010. The methods that we used are Unit Root Test, Ordinary Least Squared (OLS), Co-integration Test, and the Granger Causality Test.